The Use of Telemedicine Access to Schools to Facilitate Expert Assessment of Children with Asthma - David A. Bergman; Paul J. Sharek; Kathryn Ekegren; Shannon Thyne; Michelle Mayer; Mara Saunders (International Journal of Telemedicine and Applications, 2008)
Research has shown that access to an asthma specialist improves asthma outcomes. We hypothesized that we could improve access to expert asthma care through a telemedicine link between an asthma specialist and a school-based asthma program. We conducted a prospective cohort study in 3 urban schools to ascertain the feasibility of using an asthma-focused telemedicine solution. Each subject was seen by an asthma expert at 0, 8, and 32 weeks. The assessment and recommendations for care were sent to the primary care physician (PCP) and parents were told to contact their physician for follow-up care. Eighty three subjects participated in the study. Subjects experienced improvement (P<.05) in family social activities and the number of asthma attacks. Ninety four percent of subjects rated the program as good or excellent. This study demonstrates the feasibility and acceptance of a school-based asthma program using a telemedicine link to an asthma specialist.